Aplikasi Sistem SMS Hitung Cepat Berbasis PHP dan MYSQL (Studi Kasus Suara Gerindra Dapil 1 Pada Pemilu Legislatif 2014) - Agus Subkhi Hermawan; Oky Dwi Nurhayati; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
General Election is the Indonesian greatest democracy party, which becomes an opportunity to the legislative candidates to compete. The success of the General Election is determined by the smooth running of the vote and the vote counting process. The process of organizing elections often encountered various problems, the fraud of several elements which inflate the votes in the polling stations, and corruption of the top elements’ functionary. In order to avoid those problems, a hitung cepat is needed to inform the prediction of the election result faster than the official counting by the Commission of General Election. A hitung cepat can also be the proof of the election fraud. In this case, a hitung cepat application becomes one of the solutions to finish the vote counting faster than if manual counting is used. This application will help the official supporting teams in predicting their supported legislative candidates’ winning. This application is created by using several phases; they are system designing, prototype making, implementation, and program testing. All this phases are called prototyping method. This method is appropriatefor this project because it has a fast flow to fulfill the official supporting teams need in a dynamic political condition. The application designing is modeled by the UML. This application is created by using PHP programming language to run the program itself, and supported by Gammu and MySQL to run the function of the SMS gateway. In implementation phase, the quick count application can be used to count the vote of the legistative election in 2014 General Election by using statistic method. The level of accuracy used in this study was 99% with a margin of error 1%.